IMPLEMENTASI ANALISIS DESIGN THINGKING PADA SISTEM INFORMASI PENAGIHAN PEMBAYARAN PT. AIR MINUM GIRI MENANG DI KOTA MATARAM & KABUPATEN LOMBOK BARAT - Anisah Mutmainah; Nadiyasari Agitha; Muhammad Tammami Kurniawan (Universitas Mataram, 2022)
Facing the era of sophisticated technology, PT. Giri Wins Drinking Water (PERSODA) requires good management in the management of its services, such as billing and payment services. The information system used by billing and payment services is an android application-based system and web service. The android application is used by officers to make billing directly to the public. The web service is used by assistant managers to schedule officers to do billing, monitor officers, and make reports on billing results every day. The purpose of community service is to analyze the user experience and user interface in streamlining the features of the payment billing information system of PT. Giri Wins Drinking Water. The method used to analyze problems in community service is design thinking. Design thinking is a design methodology that is oriented to user needs by implementing technology to achieve needs so as to create design solutions that are right on target. From the analysis carried out, it is known that the system is still inefficient and can be maximized by adding payment features using QR scans on the android application and adding a dashboard page to the management website system. The results of the evaluation carried out by testing the prototype using the System Usability Scale (SUS) for billing applications obtained a score of 68.25 with an acceptability level, namely marginal hight, D value scale, and adjective rating category OK and for the billing and payment management website the score was equal to 71.75 with acceptability level that is acceptable, value scale C, and adjective rating in Good category. Analyzing the user experience and user interface in streamlining the features of the payment billing information system of PT. Giri Wins Drinking Water is very necessary to be precise and in accordance with user needs.